Implementasi Tata Tertib Madrasah dalam Meningkatkan Karakter Disiplin Siswa di MA Swasta Al-Hidayah Tebo Ilir - Siti Raudhatul Jannah; Riftiyanti Savitri; Eka Susilawati (JMiE (Journal of Management in Education), 2022)
This study aims to determine the strategy of school discipline in improving the disciplinary character of students at MAS Al-Hidayah Tebo Ilir. This research uses a qualitative approach. The informant selection technique uses purposive sampling. Data collection is carried out through observation, interviews, and documentation. Data analysis using interactive model analysis techniques by Miles and Huberman. The results showed that disciplinary character building is carried out through the application of discipline and habituation of activities that form the character of the discipline, such as arriving on time, praying on time, how to dress, and other extracurricular activities.